Clinical Manifestations and Endoscopic Findings of Eosinophilic Gastroenteritis in Children - إبراهيم علي; محمد علي; قرقماز نورا (Latakia University Journal -Medical Sciences Series, 2020)
Introduction: Eosinophilic Gastroenteritis (EGE) is an inflammatory disease which is characterized by eosinophilic infiltration of the gastrointestinal tract (GI) with varying GI symptoms, in absence of parasitic infection, vasculitis, neoplasm, or other known causes of eosinophilia. Kaijser first described this disorder in 1937,and in 1970 Klein et al. defined three subtypes of this disease based on the depth of eosinophilic infiltration of the intestinal wall: mucosal disease (the most common), muscular disease, subserosal disease. Endoscopic findings are various and non-specific which may vary from normal to slightly abnormal and cases may show diffuse abnormalities. Objective: The objective of the following study is to determine the clinical manifestations and endoscopic findings of EGE. Methods: The study included 39 children (26 males -13 females) diagnosed as EGE by biopsies taken by upper endoscopy from duodenal mucosa, in Tishreen University Hospital in Lattakia between 2016-2019. We studied their clinical manifestations and endoscopic findings. Results: The results showed that eosinophilic gastroenteritis (EGE) is a rare inflammatory disorder with male preponderance, affects all ages in childhood especially under 6 years old with various manifestations: failure to thrive (59%), abdominal pain (38.4%), atopic disorders (38.46%), vomiting (23.10%), diarrhea (5.1%). Endoscopic findings could be normal or abnormal but non-specific. Conclusion: Eosinophilic gastroenteritis (EGE) is a rare inflammatory disorder with male preponderance, affects all ages in childhood. Clinical manifestations vary, failure to thrive and abdominal pain are the most common. Endoscopic findings are unspecific and may be normal.